The bone densitometry is normal in Turner syndrome prepubertal patients after height age correction - Renata Thomazini Dallago; Denise Barbieri Marmo; André Moreno Morcillo; Gil Guerra Júnior; Allan de Oliveira Santos; Marcus Vinicius Galon; Sofia Helena Valente de Lemos-Marini (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to evaluate the bone mass in prepubertal patients with Turner Syndrome (TS) according to height age (HA) and verify the influence of karyotype and adiposity. Methods: retrospective and analytical study of prepubertal TS patients. The variables analyzed were: karyotype, age at bone densitometry (BD), height, body mass index (BMI) and BD result. The result of the BD was corrected using HA. BMI and BD were calculated on Z score for chronological age (CA) and for HA. Results: thirty-seven prepubertal patients were selected and after exclusion criteria, 13 cases between 10 and 13 years old were included in the study. The BD for HA was significantly higher than for CA (0.39 ± 1.18 x −1.62 ± 1.32), without karyotype (p=0.369) and BMI (p=0.697) influence. Conclusion: prepubertal TS patients present normal BD when corrected for HA, without influence of karyotype and BMI.